2019
DOI: 10.1177/1479164119825761
|View full text |Cite
|
Sign up to set email alerts
|

Volumes of coronary plaque disease in relation to body mass index, waist circumference, truncal fat mass and epicardial adipose tissue in patients with type 2 diabetes mellitus and controls

Abstract: Objectives: Coronary atherosclerosis in patients with type 2 diabetes mellitus may be promoted by regional fat distribution. We investigated the association between anthropometric measures of obesity, truncal fat mass, epicardial adipose tissue and coronary atherosclerosis in asymptomatic patients and matched controls. Methods: We examined 44 patients and 59 controls [mean (standard deviation) age 64.4 ± 9.9 vs 61.8 ± 9.7, male 50% vs 47%, diabetes duration mean (standard deviation) 7.7 ± 1.5] with coronary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…This prompted PCAT attenuation may provide a surrogate global biomarker for underlying vascular inflammation importantly [19]. Some studies have shown that the EFV of patients with cardiovascular disease is related to the severity of the disease [20], and the EFV of patients with coronary heart disease is larger than patients without coronary heart disease [21], however some clinical studies did not find a significant correlation between the EFV and the severity of coronary artery stenosis [22], which is consistent with the results of this present study. This may indicate that in the process from subclinical atherosclerosis to non-significant stenosis, the increase in EFV has a better warning effect on atherosclerosis than the PCAT indicators, and EFV will help identify people at high risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted PCAT attenuation may provide a surrogate global biomarker for underlying vascular inflammation importantly [19]. Some studies have shown that the EFV of patients with cardiovascular disease is related to the severity of the disease [20], and the EFV of patients with coronary heart disease is larger than patients without coronary heart disease [21], however some clinical studies did not find a significant correlation between the EFV and the severity of coronary artery stenosis [22], which is consistent with the results of this present study. This may indicate that in the process from subclinical atherosclerosis to non-significant stenosis, the increase in EFV has a better warning effect on atherosclerosis than the PCAT indicators, and EFV will help identify people at high risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It must be considered that the role of BMI measurement alone is inadequate for accurately predict the disease progression in DM subjects [41]. Other parameters such as body composition, total adipose mass, visceral adiposity-accumulation of intra-abdominal fat, and muscle mass should be analyzed to describe the current condition of DM subjects [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…There is some uncertainty regarding the exact significance of EAT in the formation of CAD as some studies have indicated that there is no correlation between coronary blood flow and myocardial perfusion [ 104 , 105 ]. Gullaksen et al found no correlation between EFV (assessed by CT) and coronary plaque volume, although the authors acknowledge a small sample size and the cross-sectional nature of the study preventing a temporal relationship between EAT and CAD to be determined [ 106 ]. Even so, it seems a greater number of studies have demonstrated an increased risk profile for CVD associated with increased EAT.…”
Section: Pathophysiologic States Of Epicardial Adipose Tissuementioning
confidence: 99%